Continuous Registration of Thrombin Generation in Plasma, Its Use for the Determination of the Thrombin Potential - Hemker, H C; Wielders, S; Kessels, H; Béguin, S (Thrombosis and Haemostasis, 1993)
A method is described by which the time-course of thrombin generation in plasma can be obtained from a continuous optical density recording of p-nitroaniline (pNA) production in a 2:3 diluted plasma. A chromogenic substrate, methylmalonyl-methylanalyl-arginyl-pNA (SQ68), is used that is specifically split by thrombin but at a low rate. The thrombin that appears and disappears in the plasma does not split more than 5% of the substrate added, so the rate of substrate conversion is in good approximation proportional to the amidolytic activity in the plasma over the entire period of thrombin generation. The course of the enzyme concentration can be calculated from the amidolytic activity curve. It is shown that the thrombin generation curves obtained in this way are essentially identical to those obtained via the classical subsampling method.The presence of SQ 68 influences the amount of free thrombin that appears in plasma because it competitively inhibits the inactivation of thrombin by AT III and α2 macroglobulin. The inhibition of the thrombin peak by heparin, relative to an uninhibited control, remains unaltered by the presence of the substrate.From the course of thrombin activity and the prevailing decay constants, the course of prothrombin conversion velocity can be calculated. Prothrombin conversion was seen to be inhibited at high (>500 μM) substrate concentrations only, and experimental conditions are found under which the inhibition of the clotting process by the substrate is negligibleThe amidolytic activity is the sum of the activities of free thrombin and of the α2 macroglobulin-thrombin complex formed. Via a mathematical procedure the amount of SQ 68 that has been split by thrombin alone and not by the a2 macroglobulin-thrombin complex, can be derived from the course of the optical density.The total amount of SQ 68 eventually split by thrombin alone is proportional to the surface under the thrombin generation curve, i. e. to the time-integral of free thrombin. This value, that we call the thrombin potential (TP), directly indicates how much of any physiological substrate can potentially be split by the thrombin being generated in the plasma.